The Sequencing of a College Degree during the Transition to Adulthood: Implications for Obesity. (June 2015) - Miech, Richard Allen; Shanahan, Michael J.; Boardman, Jason; Bauldry, Shawn
In this study we consider the health implications of the sequencing of a college degree vis-à-vis familial roles during the transition to adulthood. We hypothesize that people who earned a college degree before assuming familial roles will have better health than people who earned a college degree afterwards. To test this hypothesis, we focus on obesity and use data from the National Longitudinal Study of Adolescent Health. Results show that marriage before completion of college was associated with a 50% higher probability of becoming obese when compared with marriage after completion of college. Parenthood before college completion was associated with a greater than twofold increase in the probability of becoming obese when compared to parenthood afterwards for black men. These findings suggest that the well-established association of education with health depends on its place in a sequence of roles.